Real-Time Image Processing Toolbox for All-Optical Closed-Loop Control of Neuronal Activities - Sheng, Weihao; Zhao, Xueyang; Huang, Xinrui; Yang, Yang (Frontiers in Cellular Neuroscience, 2022)
The development of in vivo imaging and optogenetic tools makes it possible to control neural circuit activities in an all-optical, closed-loop manner [1], but such applications are limited by the lack of software for online analysis of neuronal imaging data. We developed an analysis software ORCA (Online Real-time activity and offline Cross-session Analysis), which performs image registration, neuron segmentation, and activity extraction at over 100 frames per second, fast enough to support real-time detection and readout of neural activity. Our active neuron detection algorithm is purely statistical, achieving much higher speed than previous methods. We demonstrated closed-loop control of neurons that were identified on the fly, without prior recording or image processing. ORCA also includes a cross-session alignment module that efficiently tracks neurons across multiple sessions. In summary, ORCA is a powerful toolbox for fast imaging data analysis, and provides a solution for all-optical closed-loop control of neuronal activity.